Exhibitionism and Law Enforcement: Criminal Law and Islamic Criminal Law Perspectives - Nafis Str, Raihan Hadi; Azizah, Noor (Al-Adalah: Jurnal Hukum dan Politik Islam, 2024)
Law enforcement against exhibitionists is crucial in maintaining public order and morality. This study examines law enforcement against exhibitionists based on criminal law and Islamic criminal law. The research method used is normative legal research with a statute and conceptual approach. The statute approach is employed to review existing laws and regulations. In contrast, the conceptual approach explores the principles of Islamic criminal law related to law enforcement against exhibitionism. The results of this study show that in the context of general criminal law, the Indonesian Penal Code (KUHP) regulates articles that can be applied to exhibitionists. Criminal sanctions stipulated in Articles 281 and 282 of the Penal Code include imprisonment and fines for those who distribute, create, or store obscene images, including those involving exhibitionism. Article 335 of the Penal Code also regulates indecent acts in public, which can include exhibitionism. According to Islamic criminal law, the form of punishment for exhibitionist behavior isÂ jarimah ta'zir. Among the Syafi'iyah and Hanabillah scholars, it is argued that the maximum punishment is ten lashes. Meanwhile, according to the Malikiyyah scholars, the punishment of lashes may exceed this limit as long as it serves a beneficial purpose. This study concludes that law enforcement against exhibitionism requires integrating general and Islamic criminal law to create a balanced legal framework that aligns with societal values. Additionally, the importance of public awareness of the social impact of exhibitionism and participation in law enforcement is emphasized